การพัฒนาตัวบ่งชี้ความเป็นครูมืออาชีพ - สิงหเดชาสิทธิ์ สิดารัศมิ์; บวรกิติวงศ์ สุชาดา (An Online Journal of Education, 2018)
The purposes of this research were to 1) develop professional teacher indicators 2) investigate the goodness of fit of the proposed professional teacher indicators model to the empirical data. The sample in this study was 847 teachers under the jurisdiction of the Office of the Basic Education commission which were randomed by multi-stage random sampling. The research tool was professional teacher questionnaire with 98 items. The scale had content validity on the basis of the index item objective congruence was 0.60-1.00 and Cronbach’s alpha reliability coefficient of each indicators was 0.553-0.924. Data were analyzed by using descriptive statistics and Pearson correlation analysis with SPSS and second order confirmatory factor analysis with LISREL. The research results were as follows: 1) The result of professional teacher indicators consisted of 4 components: Literate Teacher, Exemplary Teacher for Teaching Development, Exemplary Good Teacher, Teacher’s Learning for Self-Improvement And 16 indicators: Pedagogical Knowledge, Pedagogical Content Knowledge, Technology Pedagogical Knowledge, Change of World Society Knowledge, Higher Order Thinking Skills, Learning Management Skills, Technology Learning Management Skills, Feedback Skills, Earnestness Teaching, Behave as a Role Model, Fairness and Gharavasa-Dhamma 4, Self-Awareness, Seek Knowledge in Change of World Society, Drive for Self-Development and Create Innovation. 2) The professional teacher indicators model was found to fit the empirical data (Chi-Square = 30.22, df = 21, p-value = 0.08765, GFI = 0.995, AGFI = 0.968, RMR = 0.0332 and RMSEA = 0.0228).